2015
DOI: 10.2214/ajr.14.13130
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Imaging Features on CT Thought to Be Associated With Femoroacetabular Impingement: A Retrospective Analysis of 473 Asymptomatic Adult Hip Joints

Abstract: Imaging features on CT that are known to be associated with FAI are common in asymptomatic adult hip joints, especially in men, with a high degree of coexistence among the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
1
19
3
Order By: Relevance
“…The prevalence of hip osteoarthritis is lower in Asian than in white populations [19,34], and some authors have reported that the low prevalence of FAI-related morphologic features in Asian populations might explain this phenomenon [11,21,44]. However, recent studies, including ours, show the opposite [25,30,31]. Our findings cannot explain the discordance between the high rate of FAI-related morphologic features and low rate of hip osteoarthritis in Asian populations [6].…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…The prevalence of hip osteoarthritis is lower in Asian than in white populations [19,34], and some authors have reported that the low prevalence of FAI-related morphologic features in Asian populations might explain this phenomenon [11,21,44]. However, recent studies, including ours, show the opposite [25,30,31]. Our findings cannot explain the discordance between the high rate of FAI-related morphologic features and low rate of hip osteoarthritis in Asian populations [6].…”
Section: Discussioncontrasting
confidence: 66%
“…Establishment of the prevalence of FAI-related morphologic features may be the first step to elucidating its natural history. A high prevalence of asymptomatic FAIrelated features has been reported in Western populations [5,10,17,22,23,26,27], but no clear consensus has been reached in Asian populations [12,21,25,30,31,44]. Previous studies of Western populations [5,10,17,22,23,26,27] reported a prevalence of 14% to 66%, with the prevalence varying according to the imaging method, population (such as an unselected population or a population consisting of athletes), sex of those analyzed, and morphologic features of interest (cam, pincer, or all types).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations